Mobilization as Communication. A Latin American contribution to the study of social movements - Sartoretto, Paola Madrid (Commons. Revista de Comunicación y Ciudadanía Digital, 2016)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–> Many scholars have noted the lack of interdisciplinary dialogue and research between the areas of social movements studies and that of media and communications. While social movement studies fail to fully analyse media practices and communicative processes in relation to mobilization, in media and communication the social and political aspects of mobilization are seldom taken into account when analysing communication in social movements. This apparent lack of dialogue is presented in the paper as a consequence of north-centred theorization in the fields of social movement studies and media and communication, which is addressed by spelling out the contribution of Latin American communication scholarship and a view of mobilization as anchored in communication. <!–EndFragment–>